ANALISIS KEPUASAN. PELANGGAN MELALUI KUALITAS PELAYANAN, EVENT DAN BRAND. COMPANY HOTEL @HOM PREMIERE TIMOHO YOGYAKARTA BY HORISON - Riska Nugraheni; Eny Kustiyah; Ida Aryati Dyah Purnomo Wulan (Jurnal AKTUAL, 2022)
The purpose the study was determine the effect of service quality variables, Events, and brand companies on customer satisfaction at Hotel Hom Premiere Timoho Yogyakarta, both individually and collectively. The research method is in the form of a quantitative approach research. The population is visitors to the hotel @HOM Premiere Timoho Yogyakarta and the number of samples is 100 respondents with the research sampling technique is simple random sampling. Processing the data using the SPSS program using multiple regression equation analysis tools, t test, F test and coefficient of determination(R2) test. The results of the analysis of the results of the F test can be obtained that the quality of services, Events, and brand companies have a significant effect on customer satisfaction at the Hotel @HOM Premiere Timoho Yogyakarta together. The results of the t-test indicate that the service quality, Event, and Brand. Company variables have a significant influence on individual customer satisfaction at Hotel @HOM Premiere Timoho Yogyakarta. Keywords: Service Quality, Event, Brand. Company and Customer Satisfaction